Amazing peace : [compact disc, unabridged] : a Christmas poem - Angelou, Maya (Schwartz & Wade Books, 2008)
Angelou's poem celebrates the promise of peace in the holiday season. In this simple story, a family joins with their community--rich and poor, black and white, Muslim and Jew--to celebrate the holidays.